Characterization of jackfruit Artocarpus heterophyllus Lam. for economic traits in dry zones of Karnataka, India - G. Karunakaran; M. R. Dinesh; K. V. Ravishankar; K. Prakash; C. Kanupriya; Pritee Singh; M. Arivalagan; T. Ruchitha (Scientific Reports)
Abstract The study evaluated 94 jackfruit accessions of seedling origin from southern Karnataka based on thirteen quantitative fruit traits to identify promising trees. Significant variability was observed among the accessions. The average fruit weight was 5.79 ± 2.43 kg, with flake weight of 22.91 ± 7.96 g, flake thickness of 4.93 ± 1.05 mm, and flake recovery of 35.83 ± 8.09%. Positive correlations were observed between fruit weight and weights of skin, core, and flakes. Principal component analysis revealed substantial variability, with the first four principal components accounting for 94.32% of the total variation. Cluster analysis grouped the accessions into four distinct categories, confirming their diverse characteristics. Eleven accessions with superior commercial traits underwent biochemical and sensory evaluation, exhibiting elevated levels of flavonoids, vitamin C, carotenoids, lycopene, and antioxidant activity, especially in yellowish-orange and orange-colored flakes. Genetic diversity among these accessions was analyzed using 20 microsatellite markers, which amplified 192 alleles with an average of 9.6 alleles per locus. This work provides vital insights into jackfruit genetic diversity, in situ evaluation, and selection indices for elite trees, supporting the conservation and sustainable utilization of available genetic resources in the region.